First principles study for band engineering of MoS2 monolayer with Mn doping. (March 2020) - Han, Xiaoping; Amrane, Noureddine; Zhang, Zongsheng; Benkraouda, Maamar
Abstract: The electronic properties of MoS2 monolayer with various levels of Mn incorporation are investigated using the Heyd-Scuseria-Enrzerhof hybrid functional. Four Mn doping concentrations are considered: 2.78%, 6.25%, 11% and 25%. Results show that, with the increasing Mn doping, the Mn-induced intermediate band (IB) ranges from the localized to dispersive states, effectively acting as a stepping stone to help relay valence electrons to the conduction band. Simultaneously, the IB divides the band gap into narrower subgaps, inducing significant band-gap reduction. The combined effects of the IB widening and the band-gap narrowing engineer the band structure to extend the optical absorption of MoS2 monolayer into the long-wavelength region of solar irradiance. Detailed formation-energy calculations reveal a high favorability for Mn to substitute Mo in MoS2 monolayer under the Mo-poor condition. This work provides a fundamental guidance for broadening the functional applications of MoS2 monolayer in photocatalysis, photovoltaic cells and other photonic devices. Highlights: MoS2 monolayers with various levels of Mn doping are studied from first principles. The Mn-induced intermediate band becomes dispersive with the increasing Mn doping. The high-concentration Mn doping enhances the optical absorption of MoS2 monolayer. This work offers promise for broadening functional applications of MoS2 monolayer.